The Effectiveness of Virtual Events During Covid-19 Pandemics - Ton, Han Nu Ngoc; Do, Quynh Hai Xuan (Advances in Social Sciences Research Journal, 2022)
Events suffer from severe impacts of COVID-19 restrictions on mass gatherings. The industry shifts to digital environment to sustain. However, virtual events’ limitation is multi-dimensional interaction resulting in consumer experience and satisfaction. Therefore, the effectiveness of virtual events is questioned. Key themes of COVID-19 impacts on the event industry and virtual event environment are review. Then, a conceptual model on event experience is applied as the theoretical framework of this research. This research is guided by the constructivism approach. Using qualitative methods and a semi-structured questionnaire, six interviews were conducted to exploit narratives on virtual event interaction and attendee experience. Data are analyzed according to three key themes of pre-, during-, and post-event experience. The incompletion of five senses in virtual event design restrains interpersonal interaction which negatively affect attendee experience. Some practices are recommended to increase virtual event’s effectiveness, including virtual avatars, three-dimensional projection, and hybrid events. Experience on virtual events is negative due to low degree of interpersonal interaction. Various application of virtual reality technology is suggested to improve effectiveness. Despite some limitations, this research has expanded the literature of virtual events.